Effect of water on lipase NS81006-catalyzed alcoholysis for biodiesel production. (July 2017) - Lv, Liangliang; Dai, Lingmei; Du, Wei; Liu, Dehua
Graphical abstract: Effect of water content on lipase NS81006–mediated methanolysis and ethanolysis of renewable oils was investigated comparatively. Further, continuous running of lipase-mediated biodiesel production from waste cooking oil was realized successfully at pilot-scale facility and effect of water content was also explored. Highlights: Effect of water on lipase-mediated methanolysis and ethanolysis for biodiesel production was comparatively studied. Effect of by-product glycerol was explored. Continuous study of lipase-mediated methanolysis of waste cooking oil was investigated at pilot-scale facility. Abstract: Biodiesel production catalyzed by free lipase has been drawing attention for its lower cost and faster reaction rate compared to immobilized lipase. It has been found that free lipase NS81006 could efficiently catalyze alkyl esters production and a certain amount of water is demonstrated to be necessary for the catalytic process. The effect of water content on liquid lipase NS81006-mediated methanolysis and ethanolysis for biodiesel production was first explored respectively in this paper. It was found that with water content ranging from 3% to 10% (based on oil weight), there was no significant difference in the final alkyl ester yield either in NS81006-mediated methanolysis or ethanolysis process, while the quality of biodiesel varied obviously. The acid value as well as the contents of monoglyceride and diglyceride were much lower in the lower water-containing system. With the water content decreasing from 10% to 3%, the acid value reduced from 8.24 to 4.89 mg KOH/g oil, and the content of MAG and DAG dropped to 0.31 and 0.22, from 0.62 and 0.74, respectively. Lipase could maintain rather good stability with proper alcohol adding strategy and the gradual reduction in biodiesel yield in the repeated uses resulted from the accumulation of by-product glycerol. The continuous running of lipase-mediated methanolysis of waste cooking oil was successfully realized at 30L reactor and a final methyl ester yield of over 90% could be obtained.